Influence of spectral properties of wavelength-locked and wavelength-unlocked diode laser on fiber laser performances. (22nd June 2016) - Huang, Zhihua; Tang, Xuan; Zhao, Pengfei; Li, Zebiao; Li, Chengyu; Li, Qi; Guo, Chao; Lin, Honghuan; Wang, Jianjun; Jing, Feng
Abstract: The influence of the spectral properties of laser diode (LD) pump source, i.e. central wavelength and linewidth, on the fiber laser performances are studied. The absorption degradation ratio (ADR) is introduced and evaluated as a guide for pump selection and fiber laser design. The spectra of wavelength-locked and wavelength-unlocked LDs are measured and they are used for fiber laser amplification. The results show that the efficiency of the wavelength-locked LDs is higher than that of the wavelength-unlocked LDs at full current but the residual pump power of wavelength-locked LDs can be much higher at lower current because of the side band.